Click beetle luciferase mutant and near infrared naphthyl-luciferins for improved bioluminescence imaging - Mary P. Hall (Nature Portfolio, 2018)
Red-shifted bioluminescence emission is needed to improve deep tissue imaging resolution. Here, the authors develop a click beetle red luciferase mutant and two naphthyl-luciferin substrates, and show the ability of the new luciferin/luciferase pairing for deep tissue multispectral tomography in mice.